PENEGAKAN PERADILAN PIDANA ANAK DENGAN PENDEKATAN HUKUM PROGRESIF DALAM RANGKA PERLINDUNGAN ANAK - Setya Wahyudi (Jurnal Dinamika Hukum, 2009)
Law enforcement with progressive law approach was very fit to implements in juvenile justice enforcement, because juvenile juctice enforcement more signalyzed at juvenile protection’s interest. The relevance of proressive law enforcement with juvenile justice system in Indonesia, relied on the aim of juvenile justice system and with the existence of arrest rule, detention and penals fallout as effort and the form of sanction to juvenile, which can in treatment form which laid in juvenile justice constitution. Desire  of  criminal law  enforcement with the progressive law approach in juvenile justice system in Indonesia not yet been fully conducted, this matter is known by the police, attorney, and judge tendency, which still hold on positivistic view, so that criminal law enforcer tend to do some detention to the juvenile constitution, while sanction fallout with an eye for child protection and prosperity not yet become the especial consideration. Kata kunci: pendekatan hukum progresif, Juvenile Justice System, perlindungan anak